Pengaruh Kebijakan Dividen Terhadap Harga Saham Pada Sektor Perbankan Yang Terdaftar Di BEI Periode 2020-2024 - Amara, Gusti Ayu Vidya; Isnawati (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study was conducted to examine the effect of dividend policy on stock prices in the banking sector in Indonesia during the 2020-2024 period, amid economic uncertainty due to the COVID-19 pandemic. The purpose of this study is to determine whether dividend policy can affect stock prices, using signal theory which states that dividends serve as a positive signal to investors. This type of research is quantitative with a causal associative approach. The research sample consists of 60 banking companies listed on the Indonesia Stock Exchange and meets certain criteria. The data used is secondary data obtained from annual financial reports, stock prices, and company dividend information and the analysis technique used is simple linear regression. The results showed that the t test results showed a significance value of 0.000 <0.05, thus indicating that dividend policy has a significant effect on stock prices. This study shows that dividend policy acts as a positive signal received by the market and influences investment decisions. Banking companies should consider dividend policy carefully to increase investor confidence and support stock price stability, given the significant effect shown by dividend policy on stock prices in the capital market.